Antibiotic Sensitivity in Pseudomonas aeruginosa of DiabeticPatient’s Foot Ulcer - Apridamayanti, Pratiwi; Meilinasary, Khairunnisa Azani; Sari, Rafika (UI Scholars Hub, 2016)
Diabetes Mellitus (DM) patients are at risk to have the diabetic ulcer. The main reason for DM’s patient with ulcer complication to be treated and healed in hospital is bacterial infection. One of many bacteria that infects diabetic ulcer is Pseudomonas aeruginosa. The effort to treat this infection is by using antibiotic. The use of antibiotic unfortunately, is often found inaccurate causing the microbe resistance to occur. To choose the right antibiotic, it needs to test the antibiotic’s sensitivity towards Pseudomonas aeruginosa. The aim of this study is to determine the sensitivity of antibiotics against Pseudomonas aeruginosa. Sample used was taken from diabetic ulcers swab with grade III and IV Wagner. The identification of bacteria was managed using the biochemical test and Gram staining test. Antibiotic sensitivity was determined by Kirby Bauer method. Antibiotics that were found still sensitive towards Pseudomonas aeruginosa included ciprofloxacin, norfloxacin, imipenem, levofloxacin, meropenem, ceftriaxone, and cefotaxime, whereas cefadroxil and amikacin were resistant. Antibiotics that can be used for Pseudomonas aeruginosa in diabetic foot ulcer patients are ciprofloxacin, norfloxacin, imipenem, levofloxacin, meropenem, ceftriaxone, and cefotaxime.